Pemberian Makan Bayi dan Anak (PMBA) dengan Kejadian Stunting - Idawati, Idawati; Rosmawardiani, Rosmawardiani; Ummi Salamah; Nasriah, Nasriah; Dian Rahayu (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Stunting, also known as short toddler syndrome, is the most prevalent type of malnutrition (PE/micronutrients), which affects infants before and shortly after birth and causes their height to be out of proportion to their age. A chronic nutritional issue that results in stunting in children is insufficient dietary intake. Stunting needs special care because it can harm children's mental development and increase their risk of dying. One effort to build knowledge and skills in aiding in the resolution of dietary challenges is counseling training on Infant and Child Feeding (IYCF). The problem of stunting often arises due to a lack of knowledge and skills in meeting the nutritional needs of toddlers. “The global prevalence of stunting in the world, including in Indonesia, is still high”. To increase the community's knowledge and skills to deal with nutritional problems independently. Literature study by comparing 20 publications with similar subject matter related to knowledge and procedures of eating babies and kids and to the rate of stunting. From 9 relevant journals it was stated that Infant and Child Feeding affected increasing mothers' knowledge in preventing stunting. There is an influence of “Infant and Child Feeding (PMBA) on the incidence of stunting.